Efeitos da pronação aumentada sobre a biomecânica da marcha de indivíduos adultos jovens saudáveis e indivíduos com osteoartrite de joelho - Renan Alves Resende (2014)
Two repeated measures studies were implemented in the human mobility research laboratory of the Queens University. Two types of sandals were specifically designed for the study. The individuals walked on 3 different conditions. The study had 1 control condition (flat sandals) and 2 conditions which increased foot pronation (wedged sandal on the knee OA side and wedged sandal on the knee OA conrtralateral side right lower limb used as a reference for the study with the young individuals). The order of data collection was randomized. A motion analysis system and 6 force platforms were used to collect the data. After each condition, the subject was asked about his knee pain and comfort while walking with the previous pair of sandals. Principal component analysis and repeated measures one-way ANOVA were used to identify differences between conditions. The results of the first study demonstrated that on the ipsilateral side, the wedged sandal increased ankle eversion moment (p<0.001); rearfoot eversion (p<0.001); reduced knee internal rotation moment in late stance (p<0.001); increased and reduced knee internal rotation during early and late stance, respectively (p<0.001); reduced hip internal rotation moment during late stance (p=0.001); and increased pelvic ipsilateral drop (p=0.02). On the contralateral side, the laterally wedged sandal increased pelvic contralateral drop (p=0.001); increased hip adduction moment throughout stance (p=0.027); increased knee adduction moment in early stance (p<0.001); and increased knee frontal plane range of motion (p=0.017). The results of the second study demonstrated that on the ipsilateral side, the wedged sandal increased ankle eversion moment (p<0.001); rearfoot eversion (p<0.001); shank internal rotation (p<0.001); reduced knee internal rotation moment (p<0.001); increased and reduced knee internal rotation during early and late stance, respectively (p=0.004); increased femur internal rotation (p<0.001); and reduced hip internal rotation moment (p=0.001). On the contralateral side, the wedged sandal increased hip adduction moment (p=0.003); and increased knee adduction moment (p=0.002). The increased hip internal rotation caused by the wedged sandal may have hampered hip external rotators action in terminal stance (internal moments) resulting in smaller hip internal rotation moments computed based on the ground reaction force (external moments). The increased pelvic contralateral drop may explain the increased hip and knee adduction moments on the contralateral lower limb. These results should be considered in individuals presenting increased foot pronation. The coupling mechanism between foot pronation and shank internal rotation also occurs in individuals with knee OA. The increased knee adduction moment on the contralateral lower limb may be a compensation for the smaller knee adduction moment on the ipsilateral lower limb. Foot motion should be evaluated in individuals with knee OA and the use of lateral wedges to reduce knee adduction moment should consider the possible deleterious effects on the transverse plane of ipsilateral lower limb and on the frontal plane of the contralateral lower limb.